Quasireversible Process of Dopamine on Copper-Nickel Hydroxide Composite/Nitrogen Doped Graphene/Nafion Modified GCE and Its Electrochemical Application - Chuan-yin Liu; Zhong-yong Liu; Rong Peng; Zhi-cheng Zhong (Journal of Analytical Methods in Chemistry)
Cu-Ni(OH)2/N-GR/Nafion/GCE has been prepared by electrodeposition and activation with NaOH. The proposed modified GCE was studied by electrochemical methods. It is found that dopamine shows favorable redox cyclic voltammetric response on the proposed modified GCE with peak separation of 25 mV and large current compared with on single-component modified GCE. The kinetic of electrode process has also been investigated with rate constant of 6.618 × 10−3 cm/s, which can be deduced to be a quasireversible or near-reversible process. The proposed method has been used for DA detection with linear range of 1.0 × 10−7 mol/L to 4.6 × 10−5 mol/L, and the detection limit is 3.3 × 10−8 mol/L. The proposed method has favorable stability and reproducibility and has also been used to determine DA in simulated samples and DA injections with favorable recoveries of 98.4% to 102.6%.